2017
DOI: 10.1038/srep45712
|View full text |Cite
|
Sign up to set email alerts
|

Fermented milk containing Lactobacillus paracasei subsp. paracasei CNCM I-1518 reduces bacterial translocation in rats treated with carbon tetrachloride

Abstract: Probiotics can prevent pathological bacterial translocation by modulating intestinal microbiota and improving the gut barrier. The aim was to evaluate the effect of a fermented milk containing Lactobacillus paracasei subsp. paracasei CNCM I-1518 on bacterial translocation in rats with carbon tetrachloride (CCl4)-induced cirrhosis. Sprague-Dawley rats treated with CCl4 were randomized into a probiotic group that received fermented milk containing Lactobacillus paracasei subsp. paracasei CNCM I-1518 in drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
(96 reference statements)
1
11
0
Order By: Relevance
“…Lactulose and polyethylene glycol are used to treat hepatic encephalopathy and could interfere with the parameters we aimed to evaluate, such as intestinal microbiota or cognitive function, and therefore many of the other related parameters, such as inflammatory response or risk of falls. Nevertheless, we would like to point out that the results from the biomarkers used in the present study that could suggest an improvement in the intestinal barrier after probiotic treatment are consistent with previous data …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Lactulose and polyethylene glycol are used to treat hepatic encephalopathy and could interfere with the parameters we aimed to evaluate, such as intestinal microbiota or cognitive function, and therefore many of the other related parameters, such as inflammatory response or risk of falls. Nevertheless, we would like to point out that the results from the biomarkers used in the present study that could suggest an improvement in the intestinal barrier after probiotic treatment are consistent with previous data …”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated a beneficial effect of certain probiotics on the intestinal barrier in several experimental and clinical settings . This finding has also been reported in models of experimental cirrhosis, in which several probiotics improved the intestinal barrier, decreased bacterial translocation, and ameliorated the proinflammatory state . However, in the study by Horvath et al in patients with cirrhosis treated with a different probiotic mixture, the authors did not observe any significant effect on gut permeability, as assessed by a panel of markers including lactulose/mannitol ratio and fecal zonulin, or inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Cultures were incubated for 48 h at 37°C in an aerobic atmosphere. The isolated bacteria were presumptively identified according to their pattern of growth and morphology (41).…”
Section: Methodsmentioning
confidence: 99%